BORDERLANDS PUBLICATIONS BY STAFF OF THE LIBRARY AND INFORMATION SCIENCE INSTITUTE AT UNIVERSITY OF SILESIA IN KATOWICE: ON THE BACKGROUND OF THE SCIENTIFIC AND DIDACTIC ACTIVITIES - GĘBOŁYŚ, ZDZISŁAW (Knygotyra, 2015)
The paper presents the Eastern borderlands issues in the publication activities of the researchers in the Institute of Library and Information Science at the University of Silesia in Katowice in the years 1974–2007. The bibliographic material was gathered, systematized and described according to descriptive (date and place of publication, author) and subject characteristics (subject, scope). There are altogether 152 publications – 13 books, 4 collective works, 133 articles and 1 review. The borderland researches are distinguished by wide subject, chronological and territorial scope. The main interests of the researchers are Old Polish period (XVI–XVIII) and the present time. The territorial scope of the publications shows that Lithuania and Ukraine are the center of their attention. The subject matter of the research includes issues of book culture, the history of individual collections, profiles of librarians and bibliophiles. Together with the bibliographical analysis there is a short historical sketch of the achievements of the Institute in the didactic and scientific field as well as the cooperation with Lithuania, Belarus and Ukraine.